Benefits of agomelatine in behavioral, neurochemical and blood brain barrier alterations in prenatal valproic acid induced autism spectrum disorder. (December 2015) - Kumar, Hariom; Sharma, B.M.; Sharma, Bhupesh
Abstract: Valproic acid administration during gestational period causes behavior and biochemical deficits similar to those observed in humans with autism spectrum disorder. Although worldwide prevalence of autism spectrum disorder has been increased continuously, therapeutic agents to ameliorate the social impairment are very limited. The present study has been structured to investigate the therapeutic potential of melatonin receptor agonist, agomelatine in prenatal valproic acid (Pre-VPA) induced autism spectrum disorder in animals. Pre-VPA has produced reduction in social interaction (three chamber social behavior apparatus), spontaneous alteration (Y-Maze), exploratory activity (Hole board test), intestinal motility, serotonin levels (prefrontal cortex and ileum) and prefrontal cortex mitochondrial complex activity (complex I, II, IV). Furthermore, Pre-VPA has increased locomotor activity (actophotometer), anxiety, brain oxidative stress (thiobarbituric acid reactive species, glutathione, and catalase), nitrosative stress (nitrite/nitrate), inflammation (brain and ileum myeloperoxidase activity), calcium levels and blood brain barrier leakage in animals. Treatment with agomelatine has significantly attenuated Pre-VPA induced reduction in social interaction, spontaneous alteration, exploratory activity intestinal motility, serotonin levels and prefrontal cortex mitochondrial complex activity. Furthermore, agomelatine also attenuated Pre-VPA induced increase in locomotion, anxiety, brain oxidative stress, nitrosative stress, inflammation, calcium levels and blood brain barrier leakage. It is concluded that, Pre-VPA has induced autism spectrum disorder, which was attenuated by agomelatine. Agomelatine has shown ameliorative effect on behavioral, neurochemical and blood brain barrier alteration in Pre-VPA exposed animals. Thus melatonin receptor agonists may provide beneficial therapeutic strategy for managing autism spectrum disorder. Highlights: Pre-VPA (Prenatal valproic acid) administration induced autism like behavior in rats. Pre-VPA has increased brain ROS, NO, Ca++, inflammation & BBB permeability. Pre-VPA has impaired GIT motility & brain mitochondrial function. Agomelatine attenuated Pre-VPA impaired behavior, biochemistry & BBB permeability. Melatonin receptors should be explored further in experimental autism.